Dielectric Metalens for Superoscillatory Focusing Based on High-Order Angular Bessel Function - Yu Li; Xinhao Fan; Yunfeng Huang; Xuyue Guo; Liang Zhou; Peng Li; Jianlin Zhao (Nanomaterials, 2022)
The phenomenon of optical superoscillation provides an unprecedented way to solve the problem of optical far-field label-free super-resolution imaging. Numerous optical devices that enable superoscillatory focusing were developed based on scalar and vector diffraction theories in the past several years. However, these reported devices are designed according to the half-wave zone method in spatial coordinates. In this paper, we propose a dielectric metalens for superoscillatory focusing based on the diffraction of angular Bessel functional phase modulated vector field, under the inspiration of the tightly autofocusing property of a radially polarized high-order Bessel beam. Based on this kind of metalens with a numerical aperture (NA) of 0.9, the linearly polarized light is converted into a radially polarized one and then focus into a superoscillating focal spot with the size of 0.32λ/NA. This angular spectrum modulation theory involved in this paper provides a different way of designing superoscillatory devices.